A Book Review on Vastipradeepam - Abhiram , Sankar R; Binitha , A (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda was side lined in the beginning of twentieth century due to the popularity and easy access to modern healthcare facilities as well as lack of enough promptness to popularize traditional health care systems. Sri C.Krishnan Vaidyan Panavally tried to make Ayurveda more popular and practical based on the principles of classical text books, through his clinical practices and books.